FROM DOMESTIC TO PUBLIC: THE CONSTRUCTION OF WOMEN'S EMPOWERMENT DISCOURSE IN SAUDI ARABIA’S VISION 2030 - Ainurrofiq, Faiq; Khasanah, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
The involvement of women in the public sphere in Saudi Arabia has increased after Crown Prince Muhammad bin Salman officially declared the vision of Saudi Arabia 2030. In contrast to Saudi Arabia's Wahhabi clerics who tend to domesticate the role of women, the government in its vision actually encourages women to be involved in the public sphere. This paper seeks to describe the discourse on women's empowerment and reveal the ideology that underlies it and to explain the implications of the construction of this discourse on changes in public policy in Saudi Arabia. The author use critical discourse analysis as an analytical tool. The author concludes, First, the discourse on women's empowerment in the Saudi 2030 vision document is manifested in giving equal roles to women and men to be involved in social and economic activities. Women in Saudi's 2030 vision are positioned as national assets that are open, competitive, hardworking, and able to drive the economy. Second, the discourse that encourages women to be involved in public activities is inseparable from the ideology of the current Saudi Arabian government which tends to lead to socio-economic liberalization. In this context, women's empowerment is used for the benefit of economic growth and the transformation of new, more open religious social conditions (infitah). Third, the discourse on women's empowerment in the Saudi 2030 vision influences changes in public policy in Saudi Arabia. The old policies from the rulings of the ulama were replaced with new policies that gave women more freedom to participate in the public sphere.